Farm aid a low cost six-row carabao-driven precision planter with seedbed maker to improve direct plating efficiency of onion farmers in Central Luzon - Barlisan, Kirsty Helena M.; Constantino, Nina Elisa B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2016)
The onion production in central Luzon is continuously threatened by importation. Maximization of farming area, efficient use of time and funds, and effective manueverability are the key to helping the farmers produce and earn more. The development of FARM AID, a low-cost onion planter, aims to combine two farm chores into one equipment, reduce the cost of production and most importantly provide the farmer a tool that is easy to operate and ergonomic. FARM AID will help sustain our country's onion supply while providing its user a troublefree and smooth work experience.
Thesis (Bachelor of Fine Arts in Industrial Design)--University of the Philippines Diliman
Bibliography : leaves 43-45.
Keywords: Planters (Agricultural machinery)